2019
DOI: 10.1007/s40272-019-00333-x
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Tolerability of Antipsychotic Medication in Individuals with Autism Spectrum Disorder: A Systematic Review and Meta-Analysis

Abstract: The Cochrane library #1 MeSH descriptor: [Safety] explode all trees #2 Safet* (Word variations have been searched) #3 Side effect* (Word variations have been searched) #4 Undesirable effect* (Word variations have been searched) #5 Toxicit* (Word variations have been searched) #6 Adverse drug reaction* (Word variations have been searched) #7 Adverse drug effect* (Word variations have been searched) #8 Adverse drug outcome* (Word variations have been searched) #9 Adverse drug event* (Word variations have been se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 81 publications
(7 reference statements)
1
17
2
2
Order By: Relevance
“…Psychopharmacological treatment, especially antipsychotics, are used more frequently in subjects with ASD than in CHR-P (Sprong et al, 2008). In our review, the proportion of ASD treated with antipsychotics was somewhat higher, (19.0-50.0% vs 7.0-34.0%), compared to prior studies (Coury et al, 2012;Downs et al, 2016;Eussen et al, 2014;Murray et al, 2014) The increased use of antipsychotics may be related to its use in the treatment of behavioural symptoms in ASD (Alfageh et al, 2019;Owen et al, 2009;Shea et al, 2004). Moreover, a recent meta-analysis showed that there is little evidence to favour the use of antipsychotics to improve attenuated psychotic symptoms in CHR-P (Davies et al, 2018).…”
Section: Discussionmentioning
confidence: 53%
“…Psychopharmacological treatment, especially antipsychotics, are used more frequently in subjects with ASD than in CHR-P (Sprong et al, 2008). In our review, the proportion of ASD treated with antipsychotics was somewhat higher, (19.0-50.0% vs 7.0-34.0%), compared to prior studies (Coury et al, 2012;Downs et al, 2016;Eussen et al, 2014;Murray et al, 2014) The increased use of antipsychotics may be related to its use in the treatment of behavioural symptoms in ASD (Alfageh et al, 2019;Owen et al, 2009;Shea et al, 2004). Moreover, a recent meta-analysis showed that there is little evidence to favour the use of antipsychotics to improve attenuated psychotic symptoms in CHR-P (Davies et al, 2018).…”
Section: Discussionmentioning
confidence: 53%
“…Parents reported the most frequent causes of drug discontinuation to be lack of efficacy and adverse events [48]. The higher rate of adverse events shown by recent meta-analyses [15,55] did not impact on discontinuation due to adverse events in our study. Moreover, according to a recent meta-analysis [60], antipsychotics had a reduced discontinuation due to lack of efficacy when compared against placebo.…”
Section: Discussioncontrasting
confidence: 44%
“…Parents could be reluctant to administer antipsychotics to their children, and concern towards adverse events often leads parents to shift towards complementary and alternative medicines [12,13]. Adverse events related to antipsychotics, such as increased appetite, weight gain, diabetes mellitus, and hyperlipidemia [14,15], may also discourage clinicians from prescribing them in children and adolescents with ASD. Adverse events can as well lead to treatment discontinuation and switch to other drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Parents reported the most frequent causes of drug discontinuation to be lack of efficacy and adverse events [48]. The higher rate of adverse events shown by recent meta-analyses [15,55] did not impact on discontinuation due to adverse events in our study. Moreover, according to a recent meta-analysis [60], antipsychotics had a reduced discontinuation due to lack of efficacy when compared against placebo.…”
Section: Discussioncontrasting
confidence: 44%
“…Parents could be reluctant to administer antipsychotics to their children, and concern towards adverse events often leads parents to prefer complementary and alternative medicines [12,13]. Adverse events related to antipsychotics, such as increased appetite, weight gain, diabetes mellitus, and hyperlipidemia [14,15], may also discourage clinicians from prescribing them in children and adolescents with ASD. Adverse events can as well lead to treatment discontinuation and switch to other drugs.…”
Section: Introductionmentioning
confidence: 99%